MENINJAU KEMBALI UNDANG-UNDANG CIPTA KERJA NOMOR 11 TAHUN 2020 TERHADAP PIHAK YANG TERDAMPAK DILIHAT DARI SUDUT PANDANG SOSIOLOGIS - Wahyu Riski Mulia; Ridho Sa’dillah Ahmad (Tahta Media Group, 2024)
This research focuses on the social and economic impact analysis of omnibus law or the copyright law of work number 11 in 2020 on Indonesian workers. Although it was designed to simplify regulations that stunted economic growth, The community's response to its implementation is uneven, especially in the context of labor.Controversy over omnibus law has emerged since the formation and confirmation stage, It's triggered by perception that those laws don't harmonize with the aspirations of society. Especially in the workforce sec. This research presents deep analysis to explore the social impacts that arise as a result of the implementation of the work's copyright laws.This research provides a broader insight into complex interactions between employment policy and social structure. Research has highlighted the inequality of people's perception of omnibus law, reflects complex social dynamics and sometimes contradicts. Especially, the impact related to the workforce becomes the main focus, With the shift in rights and the protection of the workers became a source of controversy. Although the law aims to improve the climate of investment and create jobs, This study shows that public understanding of the real consequences of these policies vary. By contributing to sociological literature related to employment policy, The journal plays an important role in understanding the social impact of policy changes. This research encourages a better understanding of how employment policies can shape and be influenced by social structures. Enrich discussions on the transformation of economic and social policy in Indonesia.